The Invention of New Methodologies: An Opportunity for Dating Natural Products - Barbazanges, Marion; Fensterbank, Louis (Synlett, 2018)
This Account surveys almost two decades of methodological developments and their straightforward applications to the total synthesis of simple natural products. The main directions covered include radical chemistry and cascades, electrophilic catalysis based on coinage metals, and asymmetric synthesis based on bis(sulfoxides) auxiliaries.1 Introduction2 Radical Cascades2.1 N-Cyanamides2.2 Homolytic Substitution at Sulfur Atom to Give Sultines3 Electrophilic Catalysis Based on Platinum(II) and Gold(I) Complexes4 From Alkylydene Bis(sulfoxides) to Chiral Carboxylic Acids5 Conclusion and Perspectives
Keywords: radical chemistry; gold catalysis; natural products; total synthesis; asymmetric synthesis; bis(sulfoxides)